2010
DOI: 10.14742/ajet.1032
|View full text |Cite
|
Sign up to set email alerts
|

Podcasting of health sciences lectures: Benefits for students from a non-English speaking background

Abstract: Podcasting in higher education is the presentation of study material in digital format that can be downloaded as audio or video files onto a MP3 player or computer. These files can then be accessed anywhere and at any time students choose. The use of podcasting is now widespread amongst undergraduate students, yet their application to the specific needs of students with a non English speaking background (NESB) is largely unknown. The findings of this study are based on a survey of 404 NESB and 708 native Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…When looking at the pattern of video accesses in this study, we observed that it peaks in parallel with the dates of each examination. This is consistent with numerous studies that report increased video accesses near the time of exams, and which indicate revision for exams as the primary motivator for using lecture capture videos [11,16,19,20,25,26,28,30,40,41]. This observation could be construed as discouraging, since the inclusive nature of the content of many courses means that lectures frequently build on content presented in previous lectures, and fewer than 12% of absences were caught up by video accesses within a week.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When looking at the pattern of video accesses in this study, we observed that it peaks in parallel with the dates of each examination. This is consistent with numerous studies that report increased video accesses near the time of exams, and which indicate revision for exams as the primary motivator for using lecture capture videos [11,16,19,20,25,26,28,30,40,41]. This observation could be construed as discouraging, since the inclusive nature of the content of many courses means that lectures frequently build on content presented in previous lectures, and fewer than 12% of absences were caught up by video accesses within a week.…”
Section: Discussionsupporting
confidence: 89%
“…Goldfarb et al [39] found that 67% of students reported not using available recordings, while Larkin [22] found that less than half the students downloaded the recordings and of those who did only 36% did so when unable to attend lecture, although both of these reports relied on subjective student reports on attendance and use of lecture capture, unlike the objective measurements presented here and in von Konski et al [16]. Some of the reported reasons for not using lecture capture videos include using other methods to catch up and not having time to listen to the recordings [40]. Although not measured objectively, students in this study frequently complained about being "too busy" to keep up with the demands of their program, so it is possible that time constraints limited accesses of the lecture videos.…”
Section: Discussionmentioning
confidence: 76%
“…Students prefer quiet locations, with easy access to their notes and relevant literature, usually listening via a stationary computer (e.g. Kazlauskas and Robinson 2012;Pearce and Scutter 2010;Popova et al 2014). This is an argument against podcasts as an application for the blurring of the place of use.…”
Section: Podcasting Not As Mobile As Expectedmentioning
confidence: 99%
“…McKenzie (2008), who studied the effectiveness of lecture-recording as a learning tool, showed that, when compared to attending face-to-face lectures, listening to lecture-recordings was at least as effective in meeting students' learning objectives as rated by students themselves. Some studies specifically looked at how lecture-recording technologies support students from non-English-language backgrounds (Leadbeater et al, 2013;Pearce & Scutter, 2010), and it was suggested that this group of students, as well as those with various disabilities (such as fatigue disorder or dyslexia), can benefit greatly from the lecturerecording opportunities (Claret, 2016).…”
Section: Lecture-recording: Benefits and Challengesmentioning
confidence: 99%